Unplanned Admissions, Emergency Department Visits, and Epilepsy After Critical Neurological Illness Requiring Prolonged Mechanical Ventilation in Children. (January 2023) - Spear, Matthew B.; Miller, Kristen; Press, Craig; Ruzas, Christopher; LaVelle, Jaime; Mourani, Peter M.; Bennett, Tellen D.; Maddux, Aline B.
Background and Purpose: Long-term outcomes after pediatric neurocritical illness are poorly characterized. This study aims to characterize the frequency and risk factors for post-discharge unplanned health resource use in a pediatric neurocritical care population using insurance claims data. Methods: Retrospective cohort study evaluating children who survived a hospitalization for an acute neurologic illness or injury requiring mechanical ventilation for >72 hours and had insurance eligibility in Colorado's All Payers Claims database. Insurance claims identified unplanned readmissions and emergency department [ED] visits during the post-discharge year. For patients without pre-existing epilepsy/seizures, we evaluated for post-ICU epilepsy identified by claim(s) for a maintenance anti-seizure medication during months 6-12 post-discharge. Multivariable logistic regression identified factors associated with each outcome. Results: 101 children, median age 3.7 years (interquartile range (IQR) .4-11.9), admitted for trauma (57%), hypoxic-ischemic injury (17%) and seizures (15%). During the post-discharge year, 4 (4%) patients died, 26 (26%) were readmitted, and 48 (48%) had an ED visit. Having a pre-existing complex chronic condition was independently associated with readmission and emergency department visit. Admission for trauma was protective against readmission. Of those without pre-existing seizures (n = 86), 25 (29%) developed post-ICU epilepsy. Acute seizures during admission and prolonged ICU stays were independently associated with post-ICU epilepsy. Conclusions: Survivors of pediatric neurocritical illness are at risk of unplanned healthcare use and post-ICU epilepsy. Critical illness risk factors including prolonged ICU stay and acute seizures may identify cohorts for targeted follow up or interventions to prevent unplanned healthcare use and post-ICU epilepsy.